Efeito da temperatura da água no desempenho e variáveis hematológicas e bioquímicas de juvenis de pacamã Lophiosilurus alexandri - Daniel Pereira da Costa (2012)
This study aimed to analyze the effects of different water temperatures on the performance, haematological and biochemistry variables of Lophiosilurus alexandri juveniles, the socalled "pacamã". The juveniles were kept in 16 tanks with a density of three juveniles/9 L of water. A period of three weeks was demanded for the animals to acclimatize to the experimental conditions. After acclimatization, juveniles of 30.61 ± 3.65 g were submitted to four water temperatures, as follows: 23, 26, 29 and 32° C with four replicates each. The temperature of each tank was gradually adjusted over two days until the desired temperature was reached. The animals were fed twice a day (8 AM and 5 PM) to feedformulation containing 43% crude protein with food equivalent to 4% of their biomass. The experiment lasted for 35 days. Data were submitted either to regression analysis or to ANOVA and subsequently to the SNK test at a 5% probability. Survival in different water temperatures was 100%. For the final weight, final length, weight gain, length gain, biomass gain, daily specific growth rate (SGR), feed conversion, and food consumption there was a quadratic effect. According to the derivation of the equations, the temperature for greatest final weight, final length, weight gain, biomass gain and SGR would be 27.7° C. As for gain in length, the best temperature was 27.3° C, whereas the best feedconversion was at 26.2° C, and dairy food consumption was 28.7°C. The viscerosomatic index was lower (P<0.05) for temperatures of 23, 26 and 19° C and higher (P<0.05) for 32° C. The hepatosomatic index was similar in the different treatments (P>0.05). Water temperature did not affect (P>0.05) the triglycerides of the L. alexandri juveniles. However, haemoglobin, plasma protein, cholesterol and haematocrit presented a quadratic effect. By derivation of the equations, the highest values of haemoglobin and haematocrit were observed at 29.4° C and 32.1° C, respectively, whereas the lower plasma protein and cholesterol would be at 23.9° C and 24.1° C, respectively. Glucose showed direct relationwith water temperature. Dissolved oxygen was inversely proportional to the increase in water temperature. The pH and total ammonia presented a quadratic effect with higher values, according to the regression equation, at 32.3° C and 28.4° C, respectively. Consequently, water temperature has an important role in the performance and causesalterations to the haematology and biochemistry of juveniles of L. alexandri, besides altering the water quality.